Modern state of bottom and demersal fish resources in the Russian waters of the Japan Sea - Pavel V. Kalchugin; Maxim I. Boyko; Sergey F. Solomatov; Emilia P. Chernienko (Известия ТИНРО, 2016)
Results of the bottom trawl survey conducted over the shelf and continental slope in the Russian waters of the Japan Sea from Peter the Great Bay to the Soya Strait in the period from March 31 to July 8, 2015 are presented. Species composition, biomass and spatial and bathymetric distribution of benthic and demersal fish are determined. Bulk of the biomass (> 90 %) was formed by 4 families: gadids, flounders, sculpins, and herrings. The species structure varied considerably by areas: pollock and plain sculpin dominated in Peter the Great Bay, pollock and sealyeye plaice - at southern Primorye beyond the Bay, herring - at northern Primorye, and sealyeye plaice and longsnout flounder - at southwestern Sakhalin. The highest density of distribution was recorded in Peter the Great Bay at the depths 500-700 m - 26.8 t/km², with domination of pollock, the lowest density was at southern Primorye in the depth range of 700-800 m - 2.4 t/km² with domination of sealyeye plaice. Peter the Great Bay was surveyed in conditions of winter distribution of fish distinguished by their high concentrations at the continental slope; their shift towards lower depths was observed at Primorye coast, and almost summer type of bathymetric distribution with the high concentrations on the shelf was found at southwestern Sakhalin. The biomass of benthic and demersal fish has increased slightly in compare with the 1980-1990s.